Mathematical Connections Related to Exponential and Logarithmic Functions: A Literature Review - Karen Gisel Campo-Meneses; Javier García-García (RANGE: Jurnal Pendidikan Matematika, 2023)
This paper reports a review of the Mathematics Education literature related to exponential and logarithmic functions and mathematical connections. Mainly, it seeks to answer the question: What is the current state of research related to exponential and logarithmic functions and mathematical connections in the field of Mathematics Education? To answer it, the systematic review was used as a method, through which a search for research focused on the preselected theme was carried out and analyzed taking into account, mainly, the objective, theoretical approach, contribution, and the reported results. This allowed, among other things, to identify what had been done to date and what would be viable studies to carry out. The results indicate that there is still much to explore in the line of mathematical connections, in addition to the need to carry out designs close to the teacher's practice, which promotes the understanding of exponential and logarithmic functions in students, based on the making of mathematical connections.